2021
DOI: 10.3390/molecules26010224
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Separation of Phytochemicals from Muehlenbeckia volcanica (Benth.) Endl. by Polarity-Stepwise Elution Counter-Current Chromatography and Their Antioxidant, Antiglycation, and Aldose Reductase Inhibition Potentials

Abstract: Muehlenbeckia volcanica (Benth.) Endl. (M. volcanica), native to South America, is a traditional Peruvian medicinal plant that has multi-therapeutic properties; however, no phytochemicals have been identified from it yet. In this study, a five-step polarity-stepwise elution counter-current chromatography (CCC) was developed using methanol/water (1:5, v/v) as the stationary phase and different ratios of n-hexane, ethyl acetate, and n-butanol as mobile phases to separate the compounds from the 70% methanol extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…While investigating other factors, this study used 75 °C, 30 min, and 500 µmol to control for variables. Trolox content was quantified using a standard curve (50–500 µmol) and detected at 291 nm using a UV spectrophotometer (UV1601, SHIMADZU, Kyoto, Japan) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…While investigating other factors, this study used 75 °C, 30 min, and 500 µmol to control for variables. Trolox content was quantified using a standard curve (50–500 µmol) and detected at 291 nm using a UV spectrophotometer (UV1601, SHIMADZU, Kyoto, Japan) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of rat lens AR and AR inhibition assay were conducted as we previously reported [11]. The eyes of 10-week Sprague-Dawley rats (250-280 g) were removed and kept at −70 • C before use.…”
Section: Ar Inhibition Assaymentioning
confidence: 99%
“…The infusion of L. meyenii is used as a traditional herb medicine in Peru to treat diabetes, cough, inflammation, diarrhea, spasm, burning sensation in the stomach, and pain in the stomach and joints [8][9][10]. In our ongoing research to screen and isolate potential anti-diabetic agents from natural products [11][12][13][14], we found that the 70% MeOH extract of L. meyenii has strong antioxidant and AR inhibitory activities [15], indicating the presence of potent antioxidants and AR inhibitors in this plant. Many diterpenoids have been previously identified from L. meyenii.…”
Section: Introductionmentioning
confidence: 99%
“…La creciente demanda mundial por productos naturales con propiedades antioxidantes, ha vuelto la mirada a la búsqueda de especies vegetales nativas, con alto contenido de antocianinas y compuestos fenólicos, capaces de reducir los radicales libres y disminuir el riesgo de enfermedades relacionadas al estrés oxidativo, y a los se les ha atribuido entre otros, actividad antiinflamatoria, antimicrobiana (Santos et al, 2014), anticancerígena (Cai et al, 2004;Garzón, 2008) y antidiabética (Wang et al, 2017;Zuo et al, 2021).…”
Section: Introductionunclassified
“…7714 (2008) que valida su potencial utilidad antiinflamatoria. A nivel internacional, Wang et al (2017) han reportado que, el extracto crudo de M. volcánica muestra una inhibición relativamente alta (65,92%) de la enzima aldosa-reductasa (AR) y posee notable actividad antioxidante confirmada por el ensayo DPPH (94,74%) y el ABTS (98,892%); recientemente Zuo et al (2021), utilizando cromatografía a contracorriente han logrado por primera vez separar e identificar seis compuestos bioactivos de hojas de M. volcánica (Ac.…”
Section: Introductionunclassified